The Role of Theory in Social Science Research (With special reference to Business and Management Studies) - Rengasamy, Dhanuskodi (IJARIIE, 2016)
Theory is a backbone of research irrespective of the nature of research whether quantitative or qualitative. It is an overview about a phenomenon that explains how or why the phenomenon occurs. The application of theory in to these researches is different but both types researches accepted theory is a vital part of social science research. Social science is one of the extensive academic disciplines, mainly concerned with society and members of the society further it focus on the relationship among individuals within the society. It has many branches each branch is called as ‘social science’. Economics is one of the main fields of social science and business and management is the subdivision of economics. The present study is mainly focus on the role of theory in these two specified studies. Most of the research reports in business and management incorporate appropriate theory in the report. As per the research methodology, the research report specifically allocates a separate heading for theory in introduct ion part or review of literature chapter. The main objective of the study is to understand the role of theory in social science research with special reference to business and management studies. The other objectives of the study are to understand the conc ept of theory in social science research, to study the application of theory in different types of research and to understand the approaches of research and theory. In quantitative research the researchers test theories an explanation to answer the research questions. In qualitative research the researchers may generate theory as final outcome of the study. Theory is an overview about a phenomenon that explains how or why the phenomenon occurs. Key word: Theory, quantitative research, qualitative research, deductive and inductive method.